ナンキョク リーセル・ラルセン ハントウ ノ ポリニア ノ スイオン コウゾウ - 牛尾, 収輝; ウシオ, シュウキ; Ushio, Shuki (2006)
P(論文) 昭和基地の西北西約200 km,南緯68度30分,東経35度00分周辺のリーセル・ラルセン半島沖に形成されるポリニア(海氷域内の開水面または疎氷域)において,海面状態と水温構造を把握するために,2000年3月から2001年1月までの間,航空機による海洋観測を行った.厳寒期のポリニア域では海氷生産が目視で確認された.AXBT(航空機投下式水温プロファイラー)による観測の結果,結氷温度に達した冬季対流混合層の深さは250-300 mであり,昭和基地北方沖ポリニアにおける混合層の深さ(約400 m)と比べて小さかった. Satellite images have suggested the presence of winter open water, or a polynya, off the Riiser-Larsen Peninsula (around 68.5°S, 35.0°E) in East Dronning Maud Land, Antarctica. To ascertain evidence for polynya formation and to survey thermal structures, the 41st Japanese Antarctic Research Expedition executed aircraft observations in 2000-2001. The observations have verified that the polynya appeared and sea ice formed in the cold season. In the polynya region, water temperature profiles were measured using an Airborne-XBT device. It is found that the winter convective-mixed layer which cooled to its freezing point reached the depth of about 250 to 300 m. The mixed layer was thinner than that of another polynya located over the shelf break around 68.5°S, 39.0°E. departmental bulletin paper